(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the legal responsibility of the state in cases of land eviction in Indonesia, particularly from the perspective of national law and human rights principles. The research method applied is normative legal research using a statutory approach, case studies, and conceptual analysis. Primary legal materials used include the 1945 Constitution, the Basic Agrarian Law (Law No. 5/1960), the Human Rights Law (Law No. 39/1999), the Land Acquisition Law (Law No. 2/2012), and the International Covenant on Economic, Social and Cultural Rights (ICESCR). Secondary sources consist of scholarly writings and previous research, while tertiary sources include dictionaries and legal encyclopedias. The results indicate that although legal instruments regulating land eviction exist, their implementation is often inconsistent with the principles of justice, legal certainty, and human rights. Forced evictions are frequently carried out without proper consultation, adequate compensation, or alternative housing solutions, thereby violating constitutional rights and international human rights obligations. Case studies such as Kampung Pulo, Bukit Duri, Rempang, and Makassar demonstrate systemic weaknesses in legal protection. The study concludes that the state has a constitutional and moral duty to respect, protect, and fulfill citizens’ land rights. Recommendations include legal reform, strengthening transparency, promoting dialogue, and ensuring fair compensation with particular attention to vulnerable groups to prevent marginalization and prolonged agrarian conflicts. Abstrak: Penelitian ini bertujuan untuk menganalisis tanggung jawab hukum negara dalam kasus penggusuran tanah di Indonesia, khususnya dari perspektif hukum nasional dan prinsip hak asasi manusia. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan, studi kasus, dan pendekatan konseptual. Bahan hukum primer meliputi UUD 1945, Undang-Undang Pokok Agraria (UU No. 5 Tahun 1960), Undang-Undang Hak Asasi Manusia (UU No. 39 Tahun 1999), Undang-Undang Pengadaan Tanah (UU No. 2 Tahun 2012), serta Kovenan Internasional Hak Ekonomi, Sosial, dan Budaya (ICESCR). Bahan hukum sekunder berasal dari literatur ilmiah, sedangkan bahan hukum tersier berupa kamus dan ensiklopedia hukum. Hasil penelitian menunjukkan bahwa meskipun instrumen hukum terkait penggusuran tanah telah ada, implementasinya sering tidak sesuai dengan prinsip keadilan, kepastian hukum, dan penghormatan HAM. Penggusuran paksa kerap dilakukan tanpa musyawarah yang efektif, kompensasi yang memadai, atau solusi relokasi, sehingga melanggar hak konstitusional dan kewajiban HAM internasional. Studi kasus di Kampung Pulo, Bukit Duri, Rempang, dan Makassar menggambarkan lemahnya perlindungan hukum bagi masyarakat. Kesimpulan penelitian ini adalah bahwa negara memiliki kewajiban konstitusional dan moral untuk menghormati, melindungi, dan memenuhi hak atas tanah warga negara. Rekomendasi penelitian ini menekankan perlunya reformasi regulasi, peningkatan transparansi, penguatan mekanisme dialog, serta pemberian ganti rugi yang adil dengan perhatian khusus pada kelompok rentan untuk mencegah marginalisasi dan konflik agraria berkepanjangan.